1996
DOI: 10.1111/j.1476-5381.1996.tb15236.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rearrangement of aminoalkylisothioureas into mercaptoalkylguanidines, a novel class of nitric oxide synthase inhibitors with selectivity towards the inducible isoform

Abstract: 1 The generation of nitric oxide (NO) from L-arginine by NO synthases (NOS) can be inhibited by guanidines, amidines and S-alkylisothioureas. Unlike most L-arginine based inhibitors, however, some guanidines and S-alkylisothioureas, in particular aminoethylisothiourea (AETU), show selectivity towards the inducible isoform (iNOS) over the constitutive isoforms (endothelial, ecNOS and brain isoform, bNOS) and so may be of therapeutic benefit. In the present study we have investigated the effects of AETU and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 40 publications
3
50
1
Order By: Relevance
“…These observations indicate that MEG is not a direct scavenger of NO. We have previously demonstrated that MEG enhances the endothelium-dependent relaxations in response to acetylcholine (46), a finding that we were unable to explain at that point. One possibility is that MEG enhances the release of NO from SNAP.…”
Section: Meg Does Not Inhibit Vascular and Cytotoxic Effects Of No-mentioning
confidence: 40%
See 4 more Smart Citations
“…These observations indicate that MEG is not a direct scavenger of NO. We have previously demonstrated that MEG enhances the endothelium-dependent relaxations in response to acetylcholine (46), a finding that we were unable to explain at that point. One possibility is that MEG enhances the release of NO from SNAP.…”
Section: Meg Does Not Inhibit Vascular and Cytotoxic Effects Of No-mentioning
confidence: 40%
“…We have observed that, in both assays, the potencies of the free thiol-containing compounds were approximately 2 orders of magnitude greater than those that cannot undergo a rearrangement to yield free thiols (46), such as S-(dimethylaminopropyl)-AETU (Table I) and S-(dimethylaminoethyl)-AETU (data not shown). Similarly, alkylation of the sulfur (S-methyl-MEG) or its oxidation to disulfide (GED) reduced the effectiveness of the compounds as scavengers of peroxynitrite.…”
Section: Meg and Related Compounds Reduce Peroxynitrite-inducedmentioning
confidence: 95%
See 3 more Smart Citations